Survival analysis of revised 2013 FIGO staging classification of epithelial ovarian cancer and comparison with previous FIGO staging classification - Paik, E Sun (Obstet Gynecol Sci, 2015)
OBJECTIVE: To analyze the prognostic role of revised version of International Federation of Gynecology and Obstetrics (FIGO) stage (2013) in epithelial ovarian cancer and compare with previous version staging classification METHODS: We retrospectively enrolled patients with epithelial ovarian cancer treated at Samsung Medical Center from 2002 to 2012. We reclassified the patients based on the revised FIGO staging classification. RESULTS: Eight hundred seventy-eight patients were enrolled (stage I, 22.8%; stage II, 10.4%; stage III, 56.2%; stage IV, 10.7%). Previous stage IC (98, 11.1%) was subdivided into IC1 (9, 1.0%), IC2 (57, 6.4%), and IC3 (32, 4.1%). In addition, previous stage IV (94, 1.7%) was categorized into IVA (37, 4.2%) and IVB (57, 6.5%) in new staging classification. Stage IIC (66, 7.5%) has been eliminated and integrated into IIA (36, 4.1%) and IIB (55, 6.2%) in revised classification. Revised FIGO stage IC3 had significant prognostic impact on PFS (hazard ratio [HR], 3.840; 95% confidence interval [CI], 1.361 to 10.83; P=0.011) and revised FIGO stage IIIC appears to be an independent, significant poor prognostic factor for PFS (HR, 2.541; 95% CI, 1.242 to 5.200; P=0.011) but not in the case of previous version of FIGO stage IIIC (HR, 1.070; 95% CI, 0.502 to 2.281; P=0.860). However, any sub-stages of both previous and revised version in stage II and IV, there was no significant prognostic role. CONCLUSION: Revised FIGO stage has more progressed utility for informing prognosis than previous version, especially in stage I and III. For stage II and IV, further validation should be needed in large population based study in the future.